2014
DOI: 10.1176/appi.ajp.2014.13101421
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Counseling for Common Psychiatric Disorders: An Opportunity for Interdisciplinary Collaboration

Abstract: In their timely review of recent important genetic findings in psychiatric disordersspecifically, common and rare copy number variants (CNVs) in bipolar disorder, schizophrenia and autism spectrum disorders-Gershon and Alliey-Rodriguez (1) propose that these findings "must lead to profound changes" in genetic counseling and "propose that genetic counseling is more than risk prediction."The genetic counseling profession has devoted considerable attention to the process of risk communication (2) and the conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…These data support collaboration between psychiatrists and genetic counselors to provide genetic counseling services for families (J. Austin, Inglis, & Hadjipavlou, 2014), which may help to facilitate the process of adaptation to OCD. Additionally, from a broader public health perspective, this model describes how a common disease can impact individuals and their families, and how genetic counseling may be able to provide them with an additional source of support.…”
Section: Discussionsupporting
confidence: 53%
“…These data support collaboration between psychiatrists and genetic counselors to provide genetic counseling services for families (J. Austin, Inglis, & Hadjipavlou, 2014), which may help to facilitate the process of adaptation to OCD. Additionally, from a broader public health perspective, this model describes how a common disease can impact individuals and their families, and how genetic counseling may be able to provide them with an additional source of support.…”
Section: Discussionsupporting
confidence: 53%
“…However, questions remain about how to integrate genomic medicine into clinical practice, such that patients reap the greatest possible benefits from increased understanding about the role of genetics in the conditions they live with or for which they are at risk. Many commentators have suggested that perhaps the optimal strategy for effective integration of genomics into all aspects of healthcare is to develop interdisciplinary collaborations between genetic counselors and physicians, including those engaged in family practice as well as specialists (Omenn, 2000;Greendale and Pyeritz, 2001;Guttmacher et al, 2001;Erskine et al, 2013;Austin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Given growing evidence indicating that people with psychiatric disorders and their families would like to receive genetic counseling (DeLisi and Bertisch, 2006;Lyus, 2007;Austin and Honer, 2008;Peay et al, 2009), psychiatry is an area of practice that potentially presents an ideal scenario for fruitful interdisciplinary collaboration between physicians and genetic counselors (Thompson et al 2015). Indeed, clear benefits have been demonstrated for individuals who have received genetic counseling for psychiatric illnesses, including improved understanding of causes of mental illness, reduced concern about other relatives becoming affected, and feeling more hopeful, in control, better able to cope and help, and reduced anxiety, self-blame and guilt (Austin and Honer, 2008;Costain et al, 2012Costain et al, , 2014Inglis et al, 2014). The world's first specialist service providing psychiatric genetic counseling (PGC) service of its kind was established in 2012 in Vancouver, British Columbia to provide genetic counseling to individuals with mental illness and their family members.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations